Antipsychotic prescribing practices in real-life (APPREAL study): Findings from the French National Healthcare System Database (2007–2017) - Rolland, Benjamin; Dalon, Faustine; Gauthier, Noémie; Nourredine, Mikaïl; Bérard, Marjorie; Carton, Louise; Brousse, Georges; Llorca, Pierre-Michel; Jacoud, Flore; Van Ganse, Eric; Belhassen, Manon (Frontiers in Psychiatry, 2022)
BACKGROUND: Antipsychotics are used in a large variety of psychiatric and neurological disorders; investigating their use in real life is important to understand national prescribing practices, as well as to determine the levels of patient adherence. METHODS: Using a 1/97e random sample (General Sample of Beneficiaries, EGB) of the French health insurance reimbursement database, we conducted a historical cohort study on the 2007 – 2017 period. The aim was to describe the sociodemographic characteristics of patients, the types of antipsychotics dispensed, the types of prescribers, the mean doses and average durations of treatment, the co-dispensed medications, and the levels of adherence to treatment. To exclude punctual uses of antipsychotics, we selected only patients with a continuous dispensing of the same antipsychotic over at least three months. RESULTS: In total, 13,799 subjects (1.66% of the EGB sample) were included (56.0% females; mean age 55.8±19.4 years). Risperidone (19.3%), cyamemazine (18.7%), olanzapine (11.9%), tiapride (8.8%), and haloperidol (7.5%) were the five most prescribed antipsychotics. 44.9% of prescriptions were written by general practitioners, 34.1% by hospital practitioners, and 18.4% by private-practice psychiatrists. On average, the mean dispensed doses were relatively low, but the variation range was large. Long-acting forms were used in 5.4% of the sample, and clozapine in 1.3%. 34.2% of patients received more than one antipsychotic, and almost 15% were prescribed at least three concomitant antipsychotics. Paliperidone and clozapine were associated with the highest levels of adherence, and risperidone and haloperidol with the lowest ones. CONCLUSIONS: An important heterogeneity of antipsychotic prescribing practices was observed in France. The rate of use of long-acting antipsychotics was low, whereas multiple antipsychotic prescriptions were frequent.